Characteristics of Buffalo Milk Curd on Variations in Fermentation Time - HANANI, IZZAH; Dewi, Kurnia Harlina; Anggraini, Tuty (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Curd is a processed product from buffalo milk through a fermentation process. The clumping of fresh buffalo milk into curd occurs due to the presence of Lactic Acid Bacteria (LAB) in buffalo milk. Curd contains lactic acid bacteria (LAB), which are beneficial for health. These bacteria not only extend the shelf life of food by inhibiting the growth of spoilage and pathogenic bacteria but also produce bioactive compounds that are good for the body. LAB contained in curd even has probiotic properties. This research used a starter of 10% buffalo milk curd. In one production, 4500 ml of fresh buffalo milk and 500 ml of starter are used, yielding 3.8 kg of buffalo milk curd. The results of observations during 7 days of fermentation were water content (81.25-72.53%), ash content (0.93-0.89%), protein content (8.97-7.94%), fat content (7 .72-7.10%), carbohydrate content (1.13-11.54%), pH value (5.72-4.27), temperature (26.87-28.43oC), Total Lactic Acid Bacteria (1.6x109- 8.1x109 cfu/ml).